Konstantin Bol’šakov and the War - Bogomolov, Nikolaj (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Novelist and poet Kostantin Bolshakov is one of the most enigmatic figures of Russian futurism. The poems written during the First World War are among Bolshakov’s most important literary productions, which enabled him to elaborate his unique mythology and which constitute the nucleus around which he developed his most artistically significant prose works of the 1920s and 1930s.